Evaluation of the effect of healthy nutrition attitudes and sleep quality on sports performance in fencing athletes - Dogruyol, Ö.; Okburan, G.; Dogruyol, S. (Turkish Journal of Sport and Exercise, 2023)
The primary purpose of this study is to examine the attitudes of adolescent fencing athletes toward healthy eating and the effect of sleep quality on their sports performance. The study was carried out with adolescent fencing athletes who are active in Mersin Province. The study participants included 50 fencing athletes (24 females, 36 males) whose ages ranged from 12 to 18 years. The healthy eating attitudes of the participants were evaluated with the "Attitudes Towards Healthy Eating Scale", sleep quality with the "Sleep Quality and Sleep Variables Scale" and sports performance with the "Vertical Jump Test". The findings showed there were significant relationships among fencing athletes` attitudes towards information on nutrition (IN), positive nutrition (PN), malnutrition (MP), and sleep quality (p<0.05). When the vertical jump scores of the athletes were examined, it was determined that the vertical jump performances of the athletes did not differ in terms of their sleep quality (p>0.05). In addition, it was found that vertical jump performance was affected by the positive nutrition of the fencing athletes significantly (p<0.05). To conclude, it is thought that the present study will contribute to the literature by revealing the relationships between adolescent fencing athletes' attitudes toward healthy eating, sleep quality, and physical performance.